(untitled) (PANGEEA, 2025)
Current geomorphological processes in the Corridor Mureş between Aiud and Sebeş (Aiud – Sebeş Corridor). The present-day modelling of relief in this passageway is governed by several passive factors (largely sedimentary geological substrate, particularities of landform and of natural vegetation), active factors, climate features (precipitation, temperature, etc.) and land use (arable land, pasture land, hay-fields, etc.). The association of all these elements represents the morphogenetic potential of the area. Present-day modelling, which occurs on either slope of the Mureş Corridor, is shaped by a huge variety of current geomorphological processes induced by precipitation (rain-related denudation and sheet erosion, gullying and torrent), gravitation (traction transport, down-sagging, landsliding - deep-seated and superficial; rock falls), erosion and alluviation. Key-words: morphodynamic potential, present-day modelling, gravitational processes, Mureş Corridor.